The Surge of Maternal and Congenital Syphilis in a Tertiary Care Center in Bangkok, Thailand - Kunpalin, Yada; Sirisabya, Anongnart; Chaithongwongwatthana, Surasith (Thai Journal of Obstetrics and Gynaecology, 2019)
Objectives: Globally, syphilis in pregnancies remains a significant health concern, because the infection results in numerous maternal and fetal complications. However, in Thailand, documented evidence regarding the disease in the mothers and their newborns is scarce. Therefore, we conducted the study to explore the disease’s trends in the aforementioned populations. Materials and Methods: A 10-year retrospective descriptive study (1st January 2006 – 31st December 2015) was conducted at King Chulalongkorn Memorial Hospital, Bangkok, Thailand. Hospital records of syphilis-infected pregnant women and their infants were extensively reviewed by 2 obstetricians and a neonatologist. Descriptive statistics was leveraged to present patient’s demographic and syphilis-related data. Results: The percentage of syphilis-infected pregnant women increased from 0.05% in 2006 to 0.5% in 2015. Following the same trend, the percentage of infants with proven or possible congenital syphilis rose from 0% in 2006 to 0.06% and 0.13% in 2015, respectively. Interestingly, teenage pregnant women were particularly affected by the disease in the recent years; the incidence escalated from 10% to 30%. There were 16.4% (n = 12) of infected pregnant women who did not receive treatment antenatally, half of them were asymptomatic with positive serologic results (CMIA+, RPR-, TPPA+ results). Conclusion: This study adds new information regarding the surge of maternal and congenital syphilis cases particularly in young pregnant women. This update will help to increase the awareness of obstetricians regards to syphilis screening and treatment during pregnancy period. Moreover, it emphasizes the importance of medical personnel’s’ familiarity with the reverse syphilis screening algorithm before applying to clinical practice.